Pocket ACEs: Discovering new function within an old player - Leong, Matthew; Li, Xiaomo; Chaum, Manita (Frontiers in Physiology, 2023)
Angiotensin-converting enzyme (ACE) is canonically known for its role in the renin-angiotensin system (RAS) where its conversion of angiotensin I (Ang I) to the bioactive peptide angiotensin II (Ang II) helps to regulate blood pressure, electrolyte, and volume homeostasis. Further studies on ACE have shown that its enzymatic activity is relatively non-specific and functions outside of the RAS axis. Of the multiple systems it has been implicated in, ACE has been found to play an important role in the development and modulation of hematopoiesis and the immune system, both through the RAS and independently of the RAS axis.